Pengaruh Kebijakan Dana Desa Terhadap Pembangunan Desa Mutiara - Nurlaila Ridiyani Daud; Frahmawati Bumulo; Roy Hasiru (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2022)
This study aims to know the influence of village fund policy on village development in Mutiara Village, Paguyaman Sub-district, Boalemo Regency. This is a quantitative study using ex post facto method. This study uses primary data collected through the distribution of questionnaires to 41 respondents in Mutiara Village, Paguyaman Sub-district. The data analysis technique uses simple linear regression. The finding indicates that there is an influence of village fund policy ( X ) on village development ( Y ) in Mutiara Village, Paguyaman Sub-district Boalemo Regency. The influence of village fund policy ( X ) on village development ( Y ) is 78.7% while the remaining 21.3% is explained by other variables not examined in this study.